The Associations Between Cognitive Dysfunction, Stress Biomarkers, and Administered Anesthesia Type in Total Knee Arthroplasties: Prospective, Randomized Trial - (:unkn) unknown (AM SOC INTERVENTIONAL PAIN PHYSICIANS, 2019)
Background: Postoperative cognitive dysfunction (POCD) is a serious complication associated with total knee arthroplasty (TKA) and has been shown to increase the length of hospital stay, cause functional impairment, and morbidity. Objectives: We aimed to determine whether POCD is associated with the use of general or regional anesthesia in patients undergoing TKA. Our hypothesis was that POCD would be reduced in the group that received regional analgesia without any sedations. Our secondary hypothesis was POCD would be associated with biomarkers of surgical stress. Study Design: Randomized controlled study between general and spinal anesthesia. Setting: Single-centered, university hospital, from January to October 2017. Methods: A total of 112 patients were assessed for eligibility, and a total of 57 patients completed the study. We divided the patients into general and regional anesthesia groups. Blood samples were obtained preoperatively at the first intraoperative, the third and the 24th postoperative hour. C-reactive protein (CRP), cortisol, insulin, and blood glucose levels were tested. We used 4 neurocognitive tests that were administered 1 day before operation, 7 days and 30 days after operation. Main outcome measures were neurocognitive tests scores for regional anesthesia without sedation and general anesthesia groups. Cortisol, glucose, insulin, and CRP levels. Results: Patients who received regional anesthesia showed significantly higher Mini-Mental State Examination (MMSE) scored compared with the general anesthesia at the seventh day (P = 0.037). In the general anesthesia group, patients showed significantly higher variations for the Stroop number difference. There were negative correlations between MMSE scores measured at postoperative day 7 and the 1-hour intraoperative cortisol measurements (r = -0.302; P = 0.022) and 3-hour postoperative cortisol measurements (r = -0.295; P = 0.026). Limitations: A limitation was the small number of patients. Conclusions: We demonstrate that regional anesthesia results in better neurocognitive test scores than general anesthesia in patients undergoing TKA. Patients who received regional anesthesia showed lower cortisol, higher insulin, and lower glucose levels. We recommend that patients who undergo arthroplasty surgeries should receive regional anesthesia to avoid POCD at the early stages of the postoperative period.
Keywords: Cognitive dysfunction; stress biomarkers; acute pain; regional anesthesia; spinal anesthesia; FAST-TRACK HIP; GENERAL-ANESTHESIA; INSULIN-RESISTANCE; REGIONAL ANESTHESIA; JOINT ARTHROPLASTY; IMPAIRMENT; CYTOKINE; SURGERY